(untitled) (Al-Academy, 2021)
The theatrical field has witnessed a huge development that included the semantic and formal sides, considering that the theatrical experience has gone through a long period of description and the dominance of literature and linguistics, thus the theatrical experience has been open to many workings and uses of high quality in forming and composing the visual system. The semiotics had a role in presenting transformed sign forms and features generated in the theatrical space. Thus (costumes, décor, makeup, lighting, and actor) are considered elements with sign forms and attributes that together constitute integrated semiotic unit that include all the layouts in the scenographic space. The two researchers determined on semiotics due to its role that it plays in reinforcing the density of the space and producing many indications. In order to get to the objective of the research, the two researchers divided the study into a methodological framework which includes the study problem, which has been determined by the following question about the semiotics of the visual composition in the Iraqi contemporary theatrical show. It also includes the research objective, and limits and determining the most prominent terms. The two researchers, in the theoretical framework, dealt with three sections: the first section is titled the semiotics of the visual system. The second section is the sign. As for the third section, it has been dedicated for the visual composition. The most prominent indicators of the theoretical framework have also been determined. The researchers chose (Gate Seven Play) as a sample for the research. The research included the most prominent results and conclusions that contributed in crystallizing the composition from a semiotic perspective including the following conclusion: semiotics procedures and attributes contributed in opening new horizons for the elements of the visual system regarding the role of (sign, icon and symbol) in showing and reinforcing the density of the scenographic space for the Iraqi contemporary theatrical show.